"Con quella voce armonica e suadente": Stoppani's Scientific Lectures (ENTHYMEMA, 2025)
The article explores the role of Antonio Stoppani’s scientific conferences in the context of scientific dissemination between the 19th and 20th centuries. Through a detailed analysis of his lectures and their editorial circulation, the text highlights how the conference genre was a popular and influential form of scientific communication. The historical context in which Stoppani operated is reconstructed, comparing his conferences with those of other scholars and writers of the time, as well as with his most renowned works, such as Acqua ed aria and Il Bel Paese. The article examines the rhetorical and structural strategies Stoppani employed to make his lectures accessible and engaging, analyzing the transition from specialized to popularized language. Finally, it highlights the evolution of the conference genre and its impact on shaping a scientific consciousness in Italian society at the time.
Keywords: Scientific Dissemination; Public Conferences; Antonio Stoppani; Rhetoric and Comunication; Scientific Culture; Positivism